THE CONTRIBUTION OF PSYCHOMOTRICITY IN THE DEVELOPMENT OF AUTISTIC CHILDREN: A LITERATURE REVIEW - Barros, Izabel Maria de; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Introduction: The Autistic Spectrum Disorder (ASD) is characterized by neurodevelopmental alterations resulting in the loss of some abilities, affecting social interaction, as well as communication. The diagnosis must comply with criteria defined by international bodies, with a complete assessment and use of previously validated scales. The gold standard treatment is early intervention, which needs to be initiated upon suspicion. One aspect of the treatment is harm reduction in this context, it is worth highlighting the role of psychomotricity, which is a science whose object is the study of man and his relationship to his internal and external world through his moving body. Objective: To investigate, through current literature, the importance of psychomotricity in the development of children with autism spectrum disorder (ASD). Methodology: This is a literature review study based on scientific evidence. For the search, the following databases were used for the articles: Latin American and Caribbean Literature on Health Sciences Information (LILACS), Scientific Electronic Library Online (SciELO) and the descriptors: “Psychomotor”, “Autism”, “Children”, “Psychology”. Literature review: In the context of treatment, the importance of inserting psychomotricity is highlighted. Its main objective is to act based on different perspectives, such as education, re-education and psychomotor therapy, so that it presents significant results in the care of children with ASD. Among the gains of the intervention proposed by psychomotricity in the treatment of autistic children, it allows for interiorization by performing movements around itself, favoring a better motor pattern and an interaction with the world. Conclusion: Thus, the actions taken by professionals of different categories in the search to provide quality care to minimize the difficulties faced by children with ASD are highlighted, seeking the insertion of these individuals in the social context.